A review of the role of elevated temperatures on the mechanical properties of fiber-reinforced geopolymer (FRG) composites. (March 2023) - Zhao, Jitong; Trindade, Ana Carolina Constâncio; Liebscher, Marco; Silva, Flávio de Andrade; Mechtcherine, Viktor
Abstract: In recent years geopolymers (GPs) have emerged as environmentally friendly construction materials and as incombustible mineral matrices for use in fiber-reinforced composites. The incorporation of fibers, either in discrete or continuous form, changes brittle behavior to ductile or quasi-ductile, resulting in high-performance, fiber-reinforced geopolymer (FRG) composites. For a larger-scale use of FRGs in construction and infrastructure industries, the impact of elevated temperatures is an inevitable matter of concern. The results obtained from existing studies on the fire response of GP composites differ significantly due to the differences in adopted geopolymer (GP) matrix designs, fibre types and their dosage, or testing methods. Mechanical properties of FRGs, including flexural and tensile strength, fracture toughness, and compressive strength, are comprehensively reviewed at ambient and elevated temperature levels and then correlated to microstructural changes. The article at hand aims to establish a conceptual and technical novel background for the current understanding of the combined influence of such factors and deliver an in-depth review of their effects on the performance of FRG at elevated temperatures depending on the fiber typology. Significant findings show inherently superior heat resistance for FRG composites as compared to either cement or polymer-based matrices, while it requires careful compositional design for sufficient processability, effectiveness of fibers, low volume changes and strength endurance. Furthermore, pointed out are potential applications and recommendations for heat and fire resistance, all of which still need to be addressed through further experimental and numerical studies.